Measuring collaboration and creativity skills through rubrics: Experience from UTPL collaborative social networks course - Piedra Pullaguari, N. (2009)
In this paper, we introduce several rubrics to measure a set of collaborative and creativity grading. Rubrics are powerful tools for both teaching - learning and assessment. Rubrics improve communication between teachers and students. This work relates the general criteria to measure the complexity levels in the development of creativity and collaborative work competences with concrete indicators associated with the use of Social Web tools and concepts. These indicators have been used in the assessment of competences in a particular course related with the use of collaborative networks. © 2010 IEEE.